The value of high-pitch scanning with Sn100kV and ADMIRE in CT examination of tuberculous destroyed lung: Identifying the optimal combination for ultra-low-dose imaging - Dong Jiang; Lixin Qin; Wenyang Pan; Shixiang Yan (PLoS ONE, 2025)
Objective To investigate the application value of high-pitch scanning combined with energy spectrum purification using Sn100kV and ADMIRE in CT examinations of patients with tuberculous destroyed lung. Methods A total of 60 patients with sputum mycobacterium tuberculosis smear positive and diagnosed with tuberculous lung damage on imaging were prospectively collected. The first CT examination utilized a conventional scanning mode with a fixed tube voltage of 120kV, CARE Dose4D activated, reference tube current set at 70mAs, and a pitch of 1.5. The interval between the initial and follow-up CT was over three months. During the follow-up CT, a high-pitch scanning mode combined with energy spectrum purification was employed, with a fixed tube voltage of Sn100kV, CARE Dose4D activated, reference tube current set at 300mAs, and a pitch of 3.2. The remaining parameters were consistent between the two CT scans. The first CT was recorded as Group A, and the follow-up CT as Group B. After the examinations, the reconstructed layer thickness was 1.00mm, and lung window and mediastinal window images with a layer spacing of 0.7mm were obtained. The image quality of the two CT examinations was scored by three physicians using a 5-point scale. Following the scoring, the consistency of the three physicians’ scores was analyzed using the intraclass correlation coefficient.. A chief physician reviewed the lung window images from both CT scans, recorded the number of focal signs detected, and conducted Chi-square tests to compare these counts between the two groups. The CT values and noise levels in both the mediastinal window and pulmonary window were measured, SNR and CNR were calculated, and independent sample T-test was performed to analyze the differences in these parameters between the two groups. Motion artifacts in the two CT images were assessed and scored by three physicians using a 3-point values, and Mann-Whitney U test was applied to compare the scores between the groups. The radiation doses of two CT examinations was recorded, and the differences between the two groups were statistically analyzed using the Mann-Whitney U test. Data analysis was conducted using SPSS 26.0 software. Results The image quality scores of both groups were 3 points or above, meeting the requirements for clinical diagnosis. The intraclass correlation coefficient (ICC) value for the consistency analysis of the pulmonary window scores among the three physicians was 0.819 (p < 0.001), and for the mediastinal window consistency analysis, the ICC value was 0.795 (p < 0.001), indicating good consistency in the subjective score diagnosis results. The detection rate of lesion signs in Group B was higher than that in Group A, but there was no statistical difference between the two groups (p > 0.05). There was no significant difference in noise, SNR, and CNR between the two groups (p > 0.05). However, the SNR and CNR in Group B were better than those in Group A. There was no statistical difference in the CT values of the aorta and muscle between the two groups of mediastinal window images, while noise, SNR, and CNR were statistically significant (p < 0.05). Noise in Group B was higher than that in Group A, while the SNR and CNR in Group B were lower than those in Group A. The motion artifacts of the two groups were significantly different (p < 0.001), with Group A having significantly more motion artifacts than Group B. The radiation dose of the two groups was statistically different (p < 0.001), with Group B’s radiation dose reduced by 76.24% compared to Group A. Conclusion The combination of high-pitch scanning with Sn100kV and ADMIRE can be effectively used for ultra-low-dose CT examination of the tuberculous destroyed lung, obtaining satisfactory diagnostic images and reducing the occurrence of motion artifacts. This technique achieves conventional diagnostic outcomes at ultra-low doses and significantly reduces motion artifacts, holding significant potential and value for widespread clinical application in CT examinations for patients with tuberculous disfigured lung.